Pengaruh Asimetri Informasi dan Kepemilikan Manajerial Terhadap Manajemen Laba Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Sari, Dewi Maya; Ananda, Rana Fathinah; Rahmadhani, Sari Nuzullina (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
This study aims to determine the effect of information asymmetry and managerial ownership on earnings management in mining companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The population in this study are mining companies listed on the Indonesia Stock Exchange as many as 47 companies. Selection of the sample in this study using purposive sampling that samples are taken based on criteria-certain criteria. The sample in this study were 13 companies with 5 years of research so that the total data studied were 65 companies. The analysis technique used is panel data regression analysis which consists of descriptive analysis, classical assumption test, selection of panel data regression models, and hypothesis testing which is tested using Eviews 9. The results of the study using a partial test (t test) show that information asymmetry has a positive effect. and significant to earnings management. While managerial ownership has a negative and significant effect on earnings management. The results of the panel data regression showed that simultaneous asymmetry of information and kemanagerial ownership and significant effect on earnings management. jawa88